Finite-Time Stabilization-Based Adaptive Fuzzy Control Design - Chen, Bing; Lin, Chong (IEEE transactions on fuzzy systems, 2021)
This article is aimed at developing a finite-time adaptive fuzzy control strategy for a class of nonlinear strict-feedback systems. For the first time, a fast finite-time practical stability criteria is set up, which provides an effective approach to address the finite-time adaptive fuzzy control design. Furthermore, a systematic finite-time adaptive fuzzy control design procedure is developed by embedding that practical stability criteria. The closed-loop stability analysis shows that the tracking error converges to a small region around the origin in finite time. Meanwhile, all the signals in the closed-loop system are bounded. At last, the presented results are tested by a numerical example.